GIS isolation switch contact temperature wireless monitoring - Liu Haoli; Li Jiaqi; Zhang Jiuye; Zhao Yubo; Zhang Jinhua; Wang Liang (SHS Web of Conferences)
The contact temperature of GIS is an indicator that reflects contact fault information and requires real-time monitoring. There is currently no direct installation of sensors to monitor temperature. Therefore, this article proposes using multi-point temperature monitoring values on the outer shell to invert and calculate the internal temperature of GIS. In addition, the multi-point sensor on the casing has been optimized. Firstly, a finite element analysis model for the temperature field of the 500kV isolation switch chamber was established, analyzed the distribution of temperature field. The installation position of the sensor on the outer shell was determined. At the same time, conduct temperature rise tests and compare the test results with the simulation results to prove the accuracy of the simulation model. Then, SVR is used to train the correspondence between multiple temperatures of the casing, contact temperature, and external temperature. The measurement of the temperature on the shell multiplied by the ambient temperature is used for the conversion calculation of contact temperature. It was found that the average absolute error of monitoring is 0.47%. This method can save economic costs and achieve the required accuracy for engineering applications.